A 72-year-old lady with urinary incontinence: A case study - A. van der Spuy; M. Papadopoulos (AOSIS, 1999)
Urinary incontinence is a far-reaching and complex problem for older persons and has major psychosocial, economic and health consequences in affected women. The aim of this case report is to demonstrate that simple physiotherapeutic intervention can bring about dramatic improvement in the continence status of a patient and as a result improve the quality of life of such a patient. A literary review, the patient history, profile and the findings of the physical examination are presented. Physiotherapy and the outcomes are further discussed.